The Analysis of Code-Mixing in Leonardo Edwin’s YouTube Video: A Sociolinguistic Study - Vanessa Niken Amelia Sasmita (Fakultas Ilmu Budaya, 2025)
This study aims to analyze the code-mixing phenomenon carried out by Leonardo Edwin in one of his YouTube videos entitled Belanja Perabotan buat Pindahan ke Tempat Tinggal Baru. Using a sociolinguistic approach, this study employed Muysken's theory (2000) to unveil the types of code-mixing and Hoffman's theory (1991) to discover the reasons behind the use of code-mixing. The data from this study are a collection of utterances spoken by Leonardo Edwin which consists of Indonesian and English. The data were then analyzed using descriptive interpretative technique by referring to the two theoretical frameworks. The research found 45 data of code-mixing to analyze. From those data, all three types of code-mixing were found which comprised insertion, alternation, and congruent lexicalization. The most dominant type found was insertion. Meanwhile, there were 41 reasons behind the use of code-mixing whose dominant reason found was talking about a particular topic. The findings of this study indicate that Leonardo Edwin's use of code-mixing is a reflection of his multilingual background and digital social environment which then causes language mixing to occur dynamically in daily communication activities.
upload by Teddy_13.04.2026
Keywords: code-mixing; sociolinguistics; YouTube; Leonardo Edwin